FIGHT AGAINST HYPOAGREGATION AND HYPOCOAGULATION IN HYBRID REVASCULARIZATION (CAROTID ENDARTERECTOMY + PERCUTANEOUS CORONARY INTERVENTION) ACCORDING TO A.N. KAZANTSEV - Антон Николаевич Казанцев; Константин Петрович Черных; Александр Владимирович Коротких; Борис Михайлович Тайц; Денис Борисович Тайц; Олег Владимирович Гусев; Евгений Олегович Мелешин; Павел Александрович Семенов; Годерзи Шотаевич Багдавадзе; Артем Дмитриевич Абдуллаев (Медицина в Кузбассе, 2021)
Purpose – to analyze hemorrhagic complications in patients after hybrid interventions, including percutaneous coronary intervention (PCI) and carotid endarterectomy (CEE). Demonstrate a new method of hemostasis and wound drainage after CEE according to A.N. Kazantsev.